Impact of ABCB1 C3435T Polymorphism on Treatment Response of Vitamin K Antagonists: A Systematic Review and Meta-analysis - Lee, So Yeon; An, Sook Hee (Korean Journal of Clinical Pharmacy, 2022)
Objective: The aim of this study was to examine the impact of ATP-binding cassette subfamily B member 1 (ABCB1) C3435Tpolymorphism on the treatment response of patients to vitamin K antagonists (VKAs). Methods: In this systematic review and metaanalysis,the PubMed/Medline, Embase, and Cochrane Library databases were searched for eligible articles for the period up toNovember 2020. Articles that reported treatment response to VKAs according to the ABCB1 C3435T polymorphism were includedin this study. Results: A total of 13 and 9 articles were included in the systematic review and meta-analysis, respectively. The weeklymaintenance dose of warfarin was significantly lower in patients with the ABCB1 3435CT or TT polymorphism type than in thosewith the ABCB1 3435CC type (weighted mean difference [WMD], −2.53 mg/week; 95% confidence interval [CI], −3.64 to −1.43,p<0.001). However, the weekly maintenance dose of acenocoumarol was not significantly associated with the ABCB1 C3435Tpolymorphism (WMD, 1.02; 95% CI, −0.61 to 2.65, p=0.22). Conclusion: The ABCB1 C3435T polymorphism was significantlyassociated with the weekly maintenance dose of warfarin. Further research is needed to confirm the association between the ABCB1C3435T polymorphism and the incidence rate of bleeding events. KCI Citation Count: 0